KETERAMPILAN MEMBACA NYARING TEKS PERANGKAT UPACARA MENGGUNAKAN METODE DEMONSTRASI SISWA KELAS VII MTSN PAYAKUMBUH. - Wirda Linda (Menara Ilmu, 2018)
This research is caused by difficulty in reading the texts of ceremonial devices because in readingthe text of the ceremony device, the students still have difficulties in voicing letters, giving pauses,intonation, tempo and learning strategies that have not varied so students become bored and payless attention to learning to read the text of ceremonial devices. Based on the above problems, thisstudy aims to describe the ability to read aloud texts of ceremonial devices using class VII MTSNdemonstration method of Payakumbuh. Indicators assessed in this study there are three indicatorsnamely Application of tempo, intonation and pause. This research type is quantitative research ofdescriptive method. The researchers took the sample by cluster random sampling technique(random class). And the class selected as the sample is class VII.2 which amounted to 22 students.Based on the result of data analysis, it can be concluded that the average reading skill ofceremonial text device using class VII method of MTSN Payakumbuh is 81 with good qualificationin terms of first aspect, the application of tempo is 86,4 with excellent qualification. Secondly, theintonation is 87.5 with excellent qualification. Third, the pause is 73.9 with more than enoughqualification.Kata kunci : membaca, membaca nyaring, metode demonstrasi.